Analysis of statistic characteristics of climatic variables in central kazakhstan in Akmola region (Journal of Geography and Environmental Management, 2019)
The article considers the analysis of statistic features of climatic parameters in Akmola region. The approximation of time graph ofaverage monthly temperatures and amount precipitation per month using linear trends has been carried out.